2022
DOI: 10.1094/pdis-10-21-2146-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Black Root Rot (Berkeleyomyces rouxiae) on Greenhouse Hemp (Cannabis sativa) in Kentucky

Abstract: Hemp, Cannabis sativa, was reintroduced to the US in 2014 after 50 years of prohibition. Since then, growers have focused primarily on cannabinoid production using female plants. Thus, most modern hemp has been asexually propagated in greenhouses and transplanted into fields. In December 2019, a commercial transplant producer in Fayette County, Kentucky reported 30% dieback on ‘Seagull’ hemp. Plants were potted into artificial media (unknown origin) immediately upon removal from the mist bench, and symptoms de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Aura, Cichorium intybus, Citrus sp., Daucus carota, Euphorbia pulcherrima, Eucalyptus regnans, E. globulus, E. globulus, E. nitens, Lathyrus odoratus, Nicotiana tabacum, and Phaseolus vulgaris as B. rouxiae (Nel et al, 2018). New hosts of B. rouxiae including Cannabis sativa (Rahnama et al, 2022), Cucumis melo , Gossypium hirsutum (Le et al, 2022), and Lactuca sativa (Nakane et al, 2019) were found or confirmed since 2018. In this study, our results showed that B. rouxiae isolate LXBR1 from faba bean was pathogenic to chickpea, common bean, cowpea, hyacinth bean, lentil, mung bean, and rice bean, and infective to adzuki bean, pea, and soybean, whereas it could not infect wheat and maize.…”
Section: Discussionmentioning
confidence: 99%
“…Aura, Cichorium intybus, Citrus sp., Daucus carota, Euphorbia pulcherrima, Eucalyptus regnans, E. globulus, E. globulus, E. nitens, Lathyrus odoratus, Nicotiana tabacum, and Phaseolus vulgaris as B. rouxiae (Nel et al, 2018). New hosts of B. rouxiae including Cannabis sativa (Rahnama et al, 2022), Cucumis melo , Gossypium hirsutum (Le et al, 2022), and Lactuca sativa (Nakane et al, 2019) were found or confirmed since 2018. In this study, our results showed that B. rouxiae isolate LXBR1 from faba bean was pathogenic to chickpea, common bean, cowpea, hyacinth bean, lentil, mung bean, and rice bean, and infective to adzuki bean, pea, and soybean, whereas it could not infect wheat and maize.…”
Section: Discussionmentioning
confidence: 99%
“…Aura, Cichorium intybus, Citrus sp., Daucus carota, Euphorbia pulcherrima, Eucalyptus regnans, E. globulus, E. globulus, E. nitens, Lathyrus odoratus, Nicotiana tabacum, and Phaseolus vulgaris as B. rouxiae (Nel et al, 2018). New hosts of B. rouxiae including Cannabis sativa (Rahnama et al, 2022), Cucumis melo (Wang et al, 2019), Gossypium hirsutum (Le et al, 2022), and Lactuca sativa (Nakane et al, 2019) were found or confirmed since 2018. In this study, our results showed that B. rouxiae isolate LXBR1 from faba bean was pathogenic to chickpea, common bean, cowpea, hyacinth bean, lentil, mung bean, and rice bean, and infective to adzuki bean, pea, and soybean, whereas it could not infect wheat and maize.…”
Section: Discussionmentioning
confidence: 99%
“…Thielaviopsis basicola is a cosmopolitan soilborne plant pathogen that attacks more than 230 plant species and causes the disease known as black root rot, and the number of new hosts is increasing ( Pereg, 2013 ; Nakane et al., 2019 ; Le et al., 2022 ; Rahnama et al., 2022 ). The disease is characterized by black necrosis on various parts of the host roots, which leads to stunting, reduced vigor, wilt, and yield loss ( Noshad et al., 2006 ; Coumans et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%